2020
DOI: 10.1016/j.stem.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprograming via Deletion of CISH in Human iPSC-Derived NK Cells Promotes In Vivo Persistence and Enhances Anti-tumor Activity

Abstract: Highlights d Deletion of CISH in human NK cells leads to improved antitumor activity d CISH À/À NK cells demonstrate more efficient glycolytic and OxPhos activity d The improved metabolic profile is mediated by mTOR signaling d CISH À/À NK cells more effectively treat AML in vivo with longer NK cell persistence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
162
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(166 citation statements)
references
References 55 publications
4
162
0
Order By: Relevance
“…Similarly, Cish −/− NK cells proliferate better in response to low levels of IL‐15 and show greater anti‐tumor efficacy in multiple mouse models 74,75 . CISH −/− human NK cells derived from induced pluripotent stem cells (iPSCs) demonstrate superior killing of tumor cells due to an improved metabolic profile compared to WT cells 76 . Several groups have already demonstrated successful genetic targeting of CISH in human NK cells resulting in enhanced anti‐tumor efficacy using humanised tumor models 76,77 .…”
Section: Nk Cell Intracellular Checkpointsmentioning
confidence: 99%
“…Similarly, Cish −/− NK cells proliferate better in response to low levels of IL‐15 and show greater anti‐tumor efficacy in multiple mouse models 74,75 . CISH −/− human NK cells derived from induced pluripotent stem cells (iPSCs) demonstrate superior killing of tumor cells due to an improved metabolic profile compared to WT cells 76 . Several groups have already demonstrated successful genetic targeting of CISH in human NK cells resulting in enhanced anti‐tumor efficacy using humanised tumor models 76,77 .…”
Section: Nk Cell Intracellular Checkpointsmentioning
confidence: 99%
“…Another approach is to transduce the genes encoding IL-2 or IL-15 to enable self-production of these critical cytokines [161]. Similarly, genetic deletion of a negative regulator of IL-15 signaling, called cytokine-inducible SH2-containing protein or CIS, in iPSC-NK cells led to improved anti-tumor function, both in vitro and in vivo in a leukemia xenograft model [162]. The authors of this study showed that the CIS-deficient NK cells had improved metabolic fitness, caused by upregulated mTOR activity, suggesting that the mTOR inhibitors that are currently being trialed for various cancers may inadvertently dampen NK cell metabolic activity and therefore function.…”
Section: Genetic Modificationmentioning
confidence: 99%
“…5a). CISH deletion has been shown to enhance NK cell metabolism 33 . To evaluate if this was also true in T cells, after expansion T cells from these six donors were subjected to metabolic analysis using Ultra-HPLC-MS/MS with or without TCR stimulation.…”
Section: Cish Ko Enhances T Cell Expansion and Function But Not Maturmentioning
confidence: 99%